Optimised empiric triple and concomitant therapy for Helicobacter pylori eradication in clinical practice: the OPTRICON study. Issue 6 (14th January 2015) - Molina‐Infante, J.; Lucendo, A. J.; Angueira, T.; Rodriguez‐Tellez, M.; Perez‐Aisa, A.; Balboa, A.; Barrio, J.; Martin‐Noguerol, E.; Gomez‐Rodriguez, B. J.; Botargues‐Bote, J. M.; Gomez‐Camarero, J.; Huerta, A.; et al.
Summary Background Empiric triple therapy for Helicobacter pylori should be abandoned when clarithromycin resistance rate is >15–20%. Optimisation of triple therapy (high‐dose acid suppression and 14‐day duration) can increase eradication rates by 10%. Aim To compare the efficacy and safety of optimised triple (OPT‐TRI) and nonbismuth quadruple concomitant (OPT‐CON) therapies. Methods Prospective multicentre study in 16 Spanish centres using triple therapy in clinical practice. In a 3‐month two‐phase fashion, the first 402 patients received an OPT‐TRI therapy [esomeprazole (40 mg b.d.), amoxicillin (1 g b.d) and clarithromycin (500 mg b.d) for 14 days] and the last 375 patients an OPT‐CON treatment [OPT‐TRI therapy plus metronidazole (500 mg b.d)]. Results Seven‐hundred seventy‐seven consecutive patients were included (402 OPT‐TRI, 375 OPT‐CON). The OPT‐CON therapy achieved significantly higher eradication rates in the per‐protocol [82.3% (95% CI = 78–86%) vs. 93.8% (91–96%), P < 0.001] and intention‐to‐treat analysis [81.3% (78–86%) vs. 90.4% (87–93%), P < 0.001]. Adverse events (97% mild/moderate) were significantly more common with OPT‐CON therapy (39% vs. 47%, P = 0.016), but full compliance with therapy was similar between groups (94% vs. 92%, P = 0.4). OPT‐CON therapy was the only significant predictor of successful eradication (odds ratio, 2.24; 95% CI: 1.48–3.51, P < 0.001). The rate of participating centres achieving cure rates ≥90% favoured OPT‐CON therapy (OPT‐TRI 25% vs. OPT‐CON 62%). Conclusions Empiric OPT‐CON therapy achieved significantly higher cure rates (>90%) compared to OPT‐TRI therapy. Addition of metronidazole to OPT‐TRI therapy increased eradication rates by 10%, resulting in more mild adverse effects, but without impairing compliance with therapy.